The Effects of porcine intestinal mucosa products on nursery pig growth performance and feeder trough space and adjustment on finishing pigs - Myers, Amanda Jean (Kansas State University, 2011)
A total of 5,480 pigs involving 10 experiments were conducted. Experiment 1 evaluated 3 feeder gap settings: 1.27, 1.91, or 2.54 cm, while Exp. 2 evaluated the effects of feeder trough space (4.45 vs. 8.9 cm/pig) and minimum feeder gap opening of 1.27 vs. 2.54 cm. In Exp. 1, pigs fed with increasing feeder gap had decreased (linear; P < 0.03) G:F due to increased (linear; P <0.02) ADFI. In Exp. 2, there was a tendency (P = 0.08) for increased ADG as feeder trough space increased from 4.45 to 8.9 cm/pig. Pigs fed with the wide feeder gap setting had increased (P < 0.01) ADFI and decreased (P < 0.01) G:F compared to pigs with the narrow feeder gap setting. Experiments 3 and 4 were conducted to determine the effects of diet form (meal vs. pellet) and feeder design (conventional dry vs. wet-dry) on finisher pig performance. In Exp. 3, pigs fed pelleted diets or via a wet-dry feeder had greater (P < 0.07 and 0.01, respectively) ADG then those fed meal diets or with a dry feeder. Diet × feeder interactions (P < 0.02) were observed for G:F. When pelleted diets were presented in dry feeders, G:F decreased, while no difference in G:F was observed between meal and pelleted diets presented in wet-dry feeders. In Exp. 4, pigs fed with wet-dry feeders had increased (P < 0.02) ADG and ADFI compared to those with dry feeders, while pigs presented pelleted diets had improved (P = 0.05) G:F compared to those presented meal diets. Experiments 5 to 9 were conducted to determine the effects of porcine intestinal mucosa products, PEP2+, Peptone 50, and PEP-NS, on the growth performance of nursery pigs. In Exp. 5, pigs fed increasing PEP2 had increased (quadratic; P < 0.02) overall ADG, ADFI, and G:F with the greatest response observed at 4% PEP2. In Exp. 6, pigs fed PEP2 had improved (P < 0.03) G:F compared to pigs fed select menhaden fish meal (SMFM) and increasing PEP2 improved (quadratic; P < 0.04) G:F with the greatest improvement seen when diets contained 4% PEP2. In Exp. 7 pigs fed PEP2+, Peptone 50 and PEP-NS had increased (P < 0.05) ADG and ADFI compared to pigs fed a negative control diet. In Exp. 8, pigs fed diets containing 6% SMFM, PEP2+, or PEP-NS had improved (P < 0.05) ADG and ADFI compared to pigs fed the negative control or 6% Peptone 50. In Exp. 9, pigs fed increasing PEP-NS had improved (quadratic; P < 0.01) ADG and G:F, with the greatest improvement observed in pigs fed 6% PEP-NS. Experiment 10 evaluated the effects of Liquitein and PCV2/M. hyo vaccine regimen on the growth performance of weanling pigs. Overall, there were no effects of Liquitein on growth performance and vaccinated pigs had decreased (P < 0.01) ADG and ADFI compared to non-vaccinated pigs.
Keywords: Pig; Feeder; Pelleting; Fish meal; Peptide; PCV2; Animal Sciences (0475)